Clinician's pocket reference (America, 1997)
This edition of the best-selling "Scut Monkey" Handbook provides all the essential information and skills needed for effective patient care in the hospital.It thoroughly covers procedures, techniques, and patient care information and features many charts and tables for quick and easy reference The text answers common questions on lab values, medication actions and dosages, intravenous therapy, emergency care, operating room procedures, and suturing techniques.